2022
DOI: 10.1590/fst.72722
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents and bioactivities of Rosa roxburghii: a systematic review

Abstract: Rosa roxbughii Tratt (RRT) is a welcome medicinal and edible fruit with unique functions and nutrients in China. In the past decades, extensive research including chemical constituents and bioactivities of RRT were reported. A total of small 78 small molecules, such as flavonoids, organic acid, triterpenes, etc. and 11 polysaccharides have been isolated from RRT. Its antioxidant, anti-tumor and other pharmacological effects were also discovered. This paper reviews the progress of those information for the R&D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In the range of 1500–1650 cm −1 , the stretching vibration and the bending vibration peak correspond to the C=O of protein (amide I) and N–H of protein (amide II), respectively (Lei et al, 2010). These results are consistent with previous reports and also suggest that the main components of both R. roxburghii Tratt powders are carbohydrates (Wang et al, 2022; Wang, Zhang, et al, 2018). Absorption peaks in 1020.15 and 1025.94 cm −1 may indicate the presence of pyran‐type and furan‐type glucoside bonds (Wang et al, 2014).…”
Section: Resultssupporting
confidence: 93%
“…In the range of 1500–1650 cm −1 , the stretching vibration and the bending vibration peak correspond to the C=O of protein (amide I) and N–H of protein (amide II), respectively (Lei et al, 2010). These results are consistent with previous reports and also suggest that the main components of both R. roxburghii Tratt powders are carbohydrates (Wang et al, 2022; Wang, Zhang, et al, 2018). Absorption peaks in 1020.15 and 1025.94 cm −1 may indicate the presence of pyran‐type and furan‐type glucoside bonds (Wang et al, 2014).…”
Section: Resultssupporting
confidence: 93%
“…RRT is rich in many active substances such as vitamin C, polysaccharides, flavonoids, polyphenols, organic acids, etc. [ 3 , 4 , 5 ]. Modern medical research has shown that RRT has a variety of biological effects, such as immune function regulation, sedation, delaying aging, and anti-tumor effects.…”
Section: Introductionmentioning
confidence: 99%
“…Scientists have discovered numerous nutritional and medicinal elements in the fruit, including phenolics, polysaccharides, triterpenoids, superoxide dismutase, proteins, vitamins, ascorbic acid, amino acids, fatty acids, and other organic acids. These components have been proven to possess antioxidant, antiatherogenic, hypoglycemic, anti-aging, and antitumor properties [6,7]. In recent years, Chestnut rose fruit has been extensively used and harnessed in the food business to produce various types of Chestnut rose juices or beverages, owing to its potential nutritional and functional characteristics [7].…”
Section: Introductionmentioning
confidence: 99%
“…These components have been proven to possess antioxidant, antiatherogenic, hypoglycemic, anti-aging, and antitumor properties [6,7]. In recent years, Chestnut rose fruit has been extensively used and harnessed in the food business to produce various types of Chestnut rose juices or beverages, owing to its potential nutritional and functional characteristics [7]. However, processed Chestnut rose juice or beverages are especially susceptible to fraudulent activities due to the market's large size, the great pro tability of these items, and the challenges associated with identifying species in processed Chestnut rose products [8].…”
Section: Introductionmentioning
confidence: 99%